Comparison of Cosmetic Results in Children >10 Years Old Undergoing Open, Laparoscopic or Robotic-Assisted Pyeloplasty: A Multicentric Study. Issue 5 (30th May 2022) - Ghidini, Filippo; Bortot, Giulia; Gnech, Michele; Contini, Giorgia; Escolino, Maria; Esposito, Ciro; Capozza, Nicola; Berrettini, Alfredo; Masieri, Lorenzo; Castagnetti, Marco
Abstract : Purpose: Our goal was to compare surgical scars assessed by a validated patient reported outcome questionnaire in children undergoing open (OP), laparoscopic (LP), or robotic-assisted (RALP) pyeloplasty. Our secondary aim was to assess the influence on the outcomes of variables such as gender or body mass index (BMI). Materials and Methods: We conducted an observational, cross-sectional, multicentric study of patients undergoing primary pyeloplasty between age 10 and 18 years at 5 tertiary Italian institutions during the period January 2010 to December 2019. Of 227 eligible patients 114 (50%) participated. OP was performed in 37 (32%), LP in 30 (26%) and RALP in 47 (41%), After a median (IQR) followup of 5.2 (2.3–7.8) years, scars were measured and assessed by a validated Patient Scar Assessment Questionnaire. Scores were compared among techniques and in accordance with several variables. Results: The median length of the surgical scar at followup was significantly larger (p <0.0001) after OP (8.1 cm vs 1.8 cm for LP and 2.0 cm for RALP), where scar length correlated with BMI (p=0.04). Ninety patients (79%) had a Patient Scar Assessment Questionnaire score within the first quartile, the most favorable. During followup, 43 (38%) participants reported scar-related symptom. Symptoms were generally more common after OP (54% vs 30% for LP and 30% for RALP, p=0.06) and scar hyperesthesia was significantly more frequent after OP (p=0.01). Conclusions: Perception of the cosmetic outcomes in pre-adolescents and adolescents after pyeloplasty was generally good. LP achieved the best cosmetic results. OP was more commonly associated with scar-related symptoms and the size of the incision paralleled BMI.